Family job search, wage bargaining, and optimal unemployment insurance - Susanne Ek; Bertil Holmlund (Institute for the Study of Labor (IZA), 2010)
The paper develops an equilibrium search and matching model where two-person families as well as singles participate in the labor market. We show that equilibrium entails wage dispersion among equally productive risk-averse workers. Marital status as well as spousal labor market status matter for wage outcomes. In general, employed members of two-person families receive higher wages than employed singles. The model is applied to a welfare analysis of alternative unemployment insurance systems, recognizing the role of spousal employment as a partial substitute for public insurance. The optimal system involves benefit differentiation based on marital status as well as spousal labor market status. Optimal differentiation yields small welfare gains but gives rise to large wage differentials.
Keywords: J31; J64; J65; 330; Job search; wage bargaining; wage differentials; unemployment; unemployment insurance; Arbeitsplatzsuchmodell; Lohnverhandlungen; Lohndifferenzierung; Arbeitslosenversicherung; Familie; Ehe; Theorie